Development of a network game for coordination of service delivery to people with a chronic illness. (September 2017) - van den Oord, Steven; Bertels, Floris; Geurts, Jac; Lenstra, Remco; Kenis, Patrick; Cambré, Bart
Introduction: In this article, network governance is examined by using a network game that enables participants to interact and communicate about the coordination of service delivery by playing a role in a simulated organizational network. Methods: The research design can be described as a data-driven inductive approach in which data were collected during two stages based on a participatory model building approach as a form of action science. The data analysis was a reflexive and iterative process of going back and forth to the thematic analysis of the audiovisual recordings and the content analysis of the surveys. We report the interim findings as well as evaluate the network game based on two game sessions each with 18 participants held in 2017. Results: The interim findings of the two game sessions provide various instances in which participants acknowledged the validity of day-to-day practices of network governance. The findings suggest that appointing a network governance form is necessary to coordinate and integrate interactions among and between networks. Conclusion: This study presents how a gaming and simulation approach to scholars, public leaders and managers replicates the functioning of organizational networks. Moreover, the approach was experienced as being supportive for informing its participants on how organizational networks are effectively structured, governed and managed in the context of coordinated service delivery for people with a chronic illness in Flanders (Belgium). It is recommended for future research to apply a quasi-experimental research design in which dimensions of network governance are manipulated to examine the behavioral underpinnings of goal-directed networks.